Manajemen Strategis dan Daya Saing Perspektif Sekolah Menengah Kejuruan - Maksum; Singgih Aji Purnomo (STIT Muslim Asia Afrika, 2022)
This paper aims to find out the extent of the implementation of strategic management and competitiveness in an effort to improve the quality of education at SMK AL HASRA Bojong Sari Depok. From the data obtained, the research uses qualitative methods. Data collection by means of Observation, Interviews, and documentation. The data analysis technique used in the research uses Miles and Hubermen's theory with a case study research model. The results showed that SMK AL HASRA Bojong Sari Depok had implemented strategic management focusing on work units in schools in the implementation of using 3 systems, namely planning, application, and evaluation.